Valuing Illustrations in Children's Books by Pedagogical Students. Categories of Selected Illustration Solutions - Małgorzata Centner-Guz (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Picture books and illustrations provide children fine art contact and first visual communication experience. Therefore, it is important for them to have their place in the child's daily routine and to be valuable in terms of cognitive and aesthetic stimuli. A place where a toddler can experience them - next to the family home - is a kindergarten, so teachers should have the competence to introduce a child into the world of book illustration. Above all, teachers ought to express personal involvement in the evaluation of such cultural texts. The paper outlines the value of book illustrations which are perceived and preferred by people who are preparing for the profession of early childhood education teacher. The subjects assessed illustrations made in different conventions and stylistics (realistic and fantastic, classic and avant-garde) and made with various techniques (painting and graphic). The assembled lexical corpus, perceiving perceptions of the illustration, was analysed from the perspective of the category of paintings evaluation and the lexical assessment category, which expressed a personal attitude to the perceived images.